Empowering the Frontline Police Officers to Cope with Police Social Service Role Strain in China - Wang, Xiaohai (2013)
Provision of social service is one of the most significant roles of the police. A review of the related literature in policing seems to reveal that empowerment holds significance for frontline officers who are largely responsible for social service delivery. This study examines the possible relationships between police social service structural empowerment (PSSSE), police social service psychological empowerment (PSSPE) and police social service role strain (PSSRS) among frontline police officers in China. This study adopts a two-phase (quantitative and qualitative approaches) sequential explanatory design. In the first phase, a questionnaire is used to collect data from a sample of two hundred frontline community patrol officers in Shenzhen Public Security Bureau, China. After conducting the quantitative analysis, the author uses in-depth interviews to explore the nature of PSSRS, PSSSE, PSSPE from twelve selected interviewees' insights. According to the results of the survey and in-depth interviews, the participants report a comparatively high level of PSSRS and low levels of PSSSE and PSSPE. It has been found that there are significantly negative correlations between PSSSE, PSSPE and PSSRS in the Chinese police organization. The Chinese police force is suggested to provide effective interventions for individual experience of psychological empowerment and reorganize the current paramilitary-bureaucratic model by changing the management practices for structural empowerment in response to the PSSRS among frontline police officers